Time Dilation Induced by Object Motion is Based on Spatiotopic but not Retinotopic Positions - Au, Ricky K. C.; Ono, Fuminori; Watanabe, Katsumi (Frontiers in Psychology, 2012)
Time perception of visual events depends on the visual attributes of the scene. Previous studies reported that motion of object can induce an illusion of lengthened time. In the present study, we asked the question whether such time dilation effect depends on the actual physical motion of the object (spatiotopic coordinate), or its relative motion with respect to the retina (retinotopic coordinate). Observers were presented with a moving stimulus and a static reference stimulus in separate intervals, and judged which interval they perceived as having a longer duration, under conditions with eye fixation (Experiment 1) and with eye movement at same velocity as the moving stimulus (Experiment 2). The data indicated that the perceived duration was longer under object motion, and depended on the actual movement of the object rather than relative retinal motion. These results are in support with the notion that the brain possesses a spatiotopic representation regarding the real world positions of objects in which the perception of time is associated with.